2008
DOI: 10.3390/s8042480
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Comparison of ASTER and MODIS Surface Reflectance and Vegetation Index Products for Synergistic Applications to Natural Resource Monitoring

Abstract: Synergistic applications of multi-resolution satellite data have been of a great interest among user communities for the development of an improved and more effective operational monitoring system of natural resources, including vegetation and soil. In this study, we conducted an inter-comparison of two remote sensing products, namely, visible/near-infrared surface reflectances and spectral vegetation indices (VIs), from the high resolution Advanced Thermal Emission and Reflection Radiometer (ASTER) (15 m) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 38 publications
(51 reference statements)
0
36
0
Order By: Relevance
“…Huete et al [50] present the NDVI analysis and the Enhanced Vegetation Index (EVI); their results demonstrate the scientific usefulness of MODIS VI. Moreover, Miura et al [52] compared MODIS VI with the high-resolution Advanced Thermal Emission and Reflection Radiometer (ASTER) (15 m) and showed that they coincided well on a global scale.…”
Section: Datamentioning
confidence: 99%
“…Huete et al [50] present the NDVI analysis and the Enhanced Vegetation Index (EVI); their results demonstrate the scientific usefulness of MODIS VI. Moreover, Miura et al [52] compared MODIS VI with the high-resolution Advanced Thermal Emission and Reflection Radiometer (ASTER) (15 m) and showed that they coincided well on a global scale.…”
Section: Datamentioning
confidence: 99%
“…Especially, monitoring of land changes can be achieved using multi-temporal and multiresolution data (Brack, 2007;McRoberts and Tomppo, 2007;Mezned et al, 2007;Miura et al, 2008;Muukkonen and Heiskanen, 2007).…”
Section: Data Analysis 231 Ndvi and Classificationmentioning
confidence: 99%
“…Inter-sensor model equations relating IKONOS NDVI with ETM+ NDVI were also determined for multiple sensors over time. Miura et al [10] compared the products from ASTER and MODIS sensors for the visible/near-infrared surface reflectance and spectral vegetation indices (VIs), namely, NDVI and the Enhanced Vegetation Index (EVI). The results show that the surface reflectance products and NDVI of the two sensors compared well at a global scale.…”
mentioning
confidence: 99%
“…Though several studies are available for a variety of satellite sensors that have been applied to crop studies, there is no comparative work for the surface reflectance and NDVI between THEOS and Landsat 5 TM, especially for cassava and sugarcane [5][6][7][8][9][10][13][14][15][16]. Cassava and sugarcane are agricultural crops that are increasingly used for biofuels in Thailand [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation